Utilization of Coal-Mining Mud as a Safe and Environmentally Friendly Building Material - Yulianis, Yulianis; Hadif, Fauzil; Kurniawan, Reinaldy; Aslam, Izzan Nur; Alam, Pocut Nurul (Aceh International Journal of Science and Technology, 2024)
Coal-mining mud is one of the wastes that must be treated before being discharged into the environment. The mud contains a lot of heavy metals which have the potential to pollute the environment and endanger human health. On the other hand, the metal contents in the mud can be used as components to strengthen building materials such as brick. In this study, an investigation was carried out to check whether the risk of heavy metal contamination in the coal-mining mud can be minimized when the brick is produced. In addition, this study also tested whether the bricks produced from the utilization of the mud were strong enough to be used as construction materials. The results obtained indicate that metal contamination can be significantly minimized through the solidification process of brick products and is following the Indonesian national quality standards. This study also shows that even though the bricks meet the strength standard for the certain purpose applied in Indonesia, the utilization of coal-mining mud mixed with cement and sand was not sufficient to produce strong bricks even though the weight obtained was quite light.